3D multiphoton lithography using biocompatible polymers with specific mechanical properties. Issue 6 (14th May 2020) - Buchroithner, Boris; Hartmann, Delara; Mayr, Sandra; Oh, Yoo Jin; Sivun, Dmitry; Karner, Andreas; Buchegger, Bianca; Griesser, Thomas; Hinterdorfer, Peter; Klar, Thomas A.; Jacak, Jaroslaw
Abstract : Two new biocompatible polymers were designed, which can be 3D structured via multiphoton lithography. Their mechanical properties and biocompatibility were determined. Abstract : The fabrication of two- and three-dimensional scaffolds mimicking the extracellular matrix and providing cell stimulation is of high importance in biology and material science. We show two new, biocompatible polymers, which can be 3D structured via multiphoton lithography, and determine their mechanical properties. Atomic force microscopy analysis of structures with sub-micron feature sizes reveals Young's modulus values in the 100 MPa range. Assessment of biocompatibility of the new resins was done by cultivating human umbilical vein endothelial cells on two-dimensionally structured substrates for four days. The cell density and presence of apoptotic cells has been quantified.